Analysis of Employee Performance with Employee Engagement as a Mediating Variable at BPR Syariah PNM Mentari - Muhammad Haikal; Dhani Ichsanuddin Nur; Tri Kartika Pertiwi (PT. Maju Malaqbi Makkarana, 2026)
This study examines the effects of Mindset, Togetherness, and Result Oriented on Employee Performance, with Employee Engagement as a mediating variable, in BPR Syariah PNM Mentari. The research is conducted in a micro–Islamic banking context that emphasizes efficiency, service quality, and regulatory compliance, and aims to clarify the contribution of these behavioral and organizational constructs to employee outcomes. A quantitative survey design was used, with data gathered via a structured questionnaire that operationalized the constructs. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) to test direct and indirect relationships. The results reveal that (1) Result Oriented has a positive and significant effect on Employee Performance, confirming that goal clarity and disciplined execution lead to better performance; (2) Mindset does not have a direct effect on performance, but its effect through Employee Engagement is significant, indicating that Mindset influences performance only when employees are engaged; (3) Employee Engagement mediates the effect of Result Oriented on performance, improving execution; and (4) Togetherness has no direct or indirect effect on performance, suggesting that collaboration alone does not drive performance without clear goals and engagement.